#TITLE_ALTERNATIVE# - HUSNUL FIKRI (NIM: 103 13 024), ALIF
Galaxy cluster is a group of galaxies bound together by gravitational force. Galaxy clusters are commonly used in cosmological researches, such as in constraining cosmological parameters. One of the important properties of a galaxy cluster relevant for cosmological research is its total mass. There are several methods known for mass determination of a galaxy cluster, including by analyzing gas in the intracuster medium (ICM). The intracluster medium (ICM) is a superheated plasma, containing ions and free electrons with temperature reaching 107 K and capable to emit X-ray photons. ICM gas is considered to be in a hydrostatic equilibrium state. The total mass of a galaxy cluster can be obtained by analyzing the ICM gas density and temperature profiles. Chandra X-ray satellite, with a good spatial resolution (~0.5 arcsec), plays important roles in observations of galaxy clusters. Its ACIS (Advanced CCD Imaging Spectrometer) detector is capable of providing spatial and spectrum information, making Chandra very good for observing and analyzing galaxy clusters. It takes a series of reduction and extraction processes of Chandra’s data before we obtain the ICM gas density and temperature profiles. Reduction and extraction processes of Chandra’s galaxy cluster data are far from easy to learn for a new user, due to poor and unstructured documentation. Some processes need very long time to execute and require repetition in order to produce good results. For cosmological researches, that usually need a large sample of galaxy clusters, this will become a problem. The purposes of this work are to compile a more structured documentation for Chandra’s data reduction and extraction processes of galaxy clusters, to automatize data processing, and to recommend some tips to produce good gas density and temperature profile.